2023
DOI: 10.3390/ijerph20032661
|View full text |Cite
|
Sign up to set email alerts
|

The Objective Structured Clinical Examination (OSCE) in Periodontology with Simulated Patient: The Most Realistic Approach to Clinical Practice in Dentistry

Abstract: The objective structured clinical examination (OSCE) is becoming an increasingly established assessment test in dental schools. The use of simulated patients in the OSCE makes the stations more similar to clinical practice. Therefore, the student can show their technical and clinical knowledge, and certainly, their ability to manage the patient. These sorts of tests, in which simulated patients can be included, would be used before the student started clinical practice with patients and/or at the end of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Simulated patients must behave consistently with all students, including the emotions they express during the test, in order to provide a fair and objective assessment of students' skills. Actors must be prepared and trained in order to standardize their involvement, which is critical for evaluating not only the student's examination skills but also their interpersonal skills (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulated patients must behave consistently with all students, including the emotions they express during the test, in order to provide a fair and objective assessment of students' skills. Actors must be prepared and trained in order to standardize their involvement, which is critical for evaluating not only the student's examination skills but also their interpersonal skills (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The administration of OSCE adheres to fundamental principles and allows flexibility in its implementation based on targeted learning outcomes and tested competencies. The design of OSCE levels, the selection of standard cases or situations, and the assessment criteria can be tailored to emphasize specialized clinical skills or competencies related to one or more learning domains (10). The review of the literature showed that OSCE exams are regarded as an effective tool for assessing clinical competence in different dental specialties, such as restorative dentistry, prosthodontics, endodontics, periodontics, oral surgery, oral medicine, oral radiology, orthodontics, and pediatric dentistry (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation